Comparative Effect of Massage Therapy versus Kangaroo Mother Care on Body Weight and Length of Hospital Stay in Low Birth Weight Preterm Infants. (25th May 2014) - Rangey, Priya Singh; Sheth, Megha
Abstract : Background . Massage therapy (MT) and kangaroo mother care (KMC) are both effective in increasing the weight and reducing length of hospital stay in low birth weight preterm infants but they have not been compared. Aim . Comparison of effectiveness of MT and KMC on body weight and length of hospital stay in low birth weight preterm (LBWPT) infants. Method . 30 LBWPT infants using convenience sampling from Neonatal Intensive Care Unit, V.S. hospital, were randomly divided into 2 equal groups. Group 1 received MT and Group 2 received KMC for 15 minutes, thrice daily for 5 days. Medically stable babies with gestational age < 37 weeks and birth weight < 2500 g were included. Those on ventilators and with congenital, orthopedic, or genetic abnormality were excluded. Outcome measures, body weight and length of hospital stay, were taken before intervention day 1 and after intervention day 5. Level of significance was 5%. Result . Data was analyzed using SPSS16. Both MT and KMC were found to be effective in improving body weight ( P = 0.001, P = 0.001). Both were found to be equally effective for improving body weight ( P = 0.328) and reducing length of hospital stay ( P = 0.868). Conclusion . MT and KMC were found to be equally effective in improving body weight and reducing length of hospital stay. Limitation . Long term follow-up was not taken.